Biofertilizer from organic solid waste using em4 - Khafniza, Khanafiah (2013)
Bio-F Sdn. Bhd.’s missions are to be the preferred company in fertilizer industry; to provide the employees with welfares and to be responsible business citizen with a concern for the environment and the communities. Bio-F Sdn. Bhd develops business with the aim to meet 100% of market demand for agriculture purposes. It starts with (1) recycle an organic waste into beneficial matter; (2) produce an environmental friendly material to fertilize the soils and plants; (3) be a substitute to chemical fertilizer; and (4) an alternative to improve waste management. The market for fertilizer is forecast to have a volume of 183.5 million tons, an increase of 13.3% since 2010. Asia/Pacific continues to control the largest portion of fertilizer demand, primarily due to its enormous agricultural sector. Direct competitors in this business are the organic fertilizer manufacturers (using waste as the raw material to produce fertilizer) and indirect competitors are chemical fertilizer manufacturers which are producing fertilizer more costly and do not address the market’s trend towards organic, natural soil enhancers. Bio-F Sdn. Bhd. comprises of qualified and experienced individuals that excel at providing unique research and development services as it relates to organic compounds and blended biological manufacturing and distribution. Bio-F Sdn. Bhd. has increasing sales from RM 712,800.00 in year 1 to RM 1,850,725.80 in year 5 with 30% growth per year. Profit and loss, cash flow and balance sheet projection show an increasing value throughout the years. The return of investment of the company is expected in year 2, payback period takes 3.96 years, approximately 4 years and internalrate of return in year 4 and 5 is 0% and 11% respectively.